POTENSI GEOWISATA BERBASIS KENAMPAKAN TANJUNG DAN FENOMENA SHEETING JOINT TANJUNG LELAPIDE PULAU SANGIHE SULAWESI UTARA - Rachmadhan, H.D.; Adam, H.E.S.; Djaya, J.H.M. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
Geotourism is increasingly popular in modern tourism because it allows tourists to understand and appreciate the unique geological features of a region. This study aims to explore the geotourism potential based on the cape landscape and sheeting joint phenomenon on Sangihe Island, North Sulawesi. Focusing on a case study of Cape Lelapide, the research involves field surveys, rock descriptions, joint structure analysis, geotourism analysis, and literature review. The research findings indicate that Sangihe Island has significant geotourism potential due to its stunning cape landscapes and sheeting joint phenomenon. The cape landscapes offer beautiful natural scenery, while the sheeting joint phenomenon provides evidence of tectonism based on previous studies. Tectonic features are indicated by the predominant N1200E orientation of joints from 100 measurements, interpreted as resulting from northwest-southeast directed stress, suggesting the subduction of the Philippine Plate beneath the Eurasian Plate (Molucca Sea Suture). Rock distribution at Cape Lelapide includes lava igneous rocks and occurrences of Calcite Vein and several vesicular structures indicating ancient volcanic activity of Sandarumang during the Quaternary-Tertiary period. Geotourism assessment highlights significant potential across various aspects, including scientific research, education, tourism, and risk degradation. With high value in scientific and educational aspects, coupled with promising tourism potential, this location is attractive for research and learning. However, attention is needed to address degradation risks, particularly due to its coastal location exposed to high wave erosion and inadequate legal protection.